2019
DOI: 10.3847/1538-3881/ab0a56
|View full text |Cite|
|
Sign up to set email alerts
|

Protoplanetary Disk Masses from Radiative Transfer Modeling: A Case Study in Taurus

Abstract: Measuring the masses of protoplanetary disks is crucial for understanding their planet-forming potential. Typically, dust masses are derived from (sub-)millimeter flux density measurements plus assumptions for the opacity, temperature, and optical depth of the dust. Here we use radiative transfer models to quantify the validity of these assumptions with the aim of improving the accuracy of disk dust mass measurements. We first carry out a controlled exploration of disk parameter space. We find that the disk te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 132 publications
(170 reference statements)
7
39
0
Order By: Relevance
“…Some of these uncertainties, in particular on disk temperature and optical depth, can be mitigated using radiative transfer modeling (e.g. Ballering & Eisner 2019). However, the opacity of dust, reflecting both its composition and grain size distribution, remain uncertain to a large degree (e.g.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Some of these uncertainties, in particular on disk temperature and optical depth, can be mitigated using radiative transfer modeling (e.g. Ballering & Eisner 2019). However, the opacity of dust, reflecting both its composition and grain size distribution, remain uncertain to a large degree (e.g.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…There are important additional uncertainties on these values arising from uncertainties in the dust temperature, optical depth, and as previously mentioned, the true contribution from free-free emission. All of these factors contribute independently and can decrease or increase the reported values within a factor of a few (Ballering & Eisner 2019). Further, given that at the scales of the observed circumstellar disks, dust scattering can decrease the intensity at millimeter wavelengths, which are likely also optically thick, our estimates for the mass of the compact sources should be taken as conservative lower limits (Liu 2019;Ueda et al 2020).…”
Section: Masses From 3 MM Continuum Emissionmentioning
confidence: 93%
“…Before investigating the effect of a planet, we first use the HOCHUNK3D Monte Carlo ray-tracing code (Whitney et al 2013) to find an unperturbed, analytical disk model that best reproduces the observed photometric SED. We largely follow the CI Tau model in Ballering & Eisner (2019) in this step. We use a photospheric temperature of T * = 4000 K and a total luminosity of L tot = 1.18L (Andrews et al 2013); 1 we assume that 75% of this luminosity (L * = 0.89L ) comes from direct photospheric emission, while 25% (L acc = 0.30L ) comes from accretion onto the star, in order to match the modeling work of McClure et al (2013a) at λ < 1µm.…”
Section: Full-disk Casementioning
confidence: 99%
“…where c s is the sound speed, v k the Keplerian velocity, r the distance from the star, H 0 = 0.065 the aspect ratio at 1 au, and β = 0.125 the flaring index. These parameters are constrained by fitting the disk SED (Ballering & Eisner 2019). The disk profile thus does not reflect that obtained by simply taking the radiative transfer output temperature and assuming hydrostatic equilibrium.…”
Section: Full-disk Casementioning
confidence: 99%
See 1 more Smart Citation